2013
DOI: 10.3390/ijms141123011
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Chronic Cardiorenal Syndrome: Is There a Role for Oxidative Stress?

Abstract: Cardiorenal syndrome is a frequently encountered clinical condition when the dysfunction of either the heart or kidneys amplifies the failure progression of the other organ. Complex biochemical, hormonal and hemodynamic mechanisms underlie the development of cardiorenal syndrome. Both in vitro and experimental studies have identified several dysregulated pathways in heart failure and in chronic kidney disease that lead to increased oxidative stress. A decrease in mitochondrial oxidative metabolism has been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 146 publications
0
72
0
6
Order By: Relevance
“…In response, the most prominent adaptive processes accompanying HF are an increase in sympathetic tone. Increased adrenergic activity causes a reduction on the physiological role of respirasomes, and consequently mitochondrial dysfunction, and a gradual decrease in the cardiac performance [28]. The excessive sympathetic activity can induce cardiomyocyte apoptosis, hypertrophy, and focal myocardial necrosis [85].…”
Section: Heart and Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…In response, the most prominent adaptive processes accompanying HF are an increase in sympathetic tone. Increased adrenergic activity causes a reduction on the physiological role of respirasomes, and consequently mitochondrial dysfunction, and a gradual decrease in the cardiac performance [28]. The excessive sympathetic activity can induce cardiomyocyte apoptosis, hypertrophy, and focal myocardial necrosis [85].…”
Section: Heart and Oxidative Stressmentioning
confidence: 99%
“…In addition, ROS has been implicated in the induction and in the complications of cardiac and renal [27] dysfunctions related to CRS [28] through the SNS and the RAAS [29].…”
Section: Biomarkers Free Radicals and Oxidative Stress: Basic Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have reported that in patients with renal failure, an altered redox balance results from greater levels of ROS, RNS and some toxins together with an impaired antioxidant capacity. [10][11][12][13][14] An increase in reactive species is known to be involved in inflammatory glomerular injury by stimulating the overproduction of several mediators, including cytokines and chemokines. One of the most important of these mediators is nuclear factor kappa beta (NF-kb).…”
Section: Introductionmentioning
confidence: 99%